Synthesis, Crystal Structure and Fluorescent Properties of 1D New Double Chain Silver(I) Complex - Ni, Tian-Jun; Yang, Zhi-Jun; He, Guang-Jie; Wang, Ying-Ling; Huang, Qian-Qian; Yuan, Qiang-Tao (Asian Journal of Chemistry, 2015)
A novel silver(I) complex [Ag(btzx)2(NO3)]n [complex 1, where btzx = m-xylylenebis(tetrazole)] is synthesized and characterized by elemental analysis, IR, powder and single crystal X-ray diffraction. The crystal structural analysis shows that silver center is four-coordinated in a distorted tetrahedral geometry by four nitrogen atoms from four different btzx and there are very weak interactions exist between Ag(I) and NO3– anions. This complex displays a 1D ladder-like double chain framework, which is further fabricated into a 2D supramolecular framework via p–p interactions. The fluorescence properties of complex 1 were investigated.